Restauration virtuelle de l’art pariétal paléolithique : le cas de la grotte de Marsoulas - Carole Fritz; Gilles Tosello; Marc Azéma; Olivier Moreau; Guy Perazio; José Péral (In Situ)
The techniques of 3D scanning are being applied in prehistoric caves and rock-shelters with increasing success. 3D imaging can even help restore the paintings of caves damaged by weathering or by human interventions (graffiti). For the first time, the ‘virtual restoration’ of a decorated gallery was undertaken in the cave of Marsoulas. This operation required the combination of 3D technology with the results of the scientific study of the site and the decorated walls.